PENGARUH PENGALAMAN TERHADAP NIAT MENGGUNAKAN KEMBALI DENGAN KEPERCAYAAN SEBAGAI VARIABEL MEDIASI (STUDI PADA KONSUMEN GRABFOOD DI KOTA DENPASAR) - Saraswathi, Maytri Kiara; Wardana, I Made (E-Jurnal Manajemen; Vol 10 No 11 (2021)DO - 10.24843/EJMUNUD.2021.v10.i11.p03, 2021)
This study aims to explain the effect of experience on intention to reuse mediated by trust in GrabFood consumers. The research was conducted in Denpasar City with a sample of 100 respondents who were determined using purposive sampling. Data were collected through questionnaires and analyzed using path analysis techniques and Sobel test. The results of this study have shown that experience has a positive and significant effect on intention to reuse. Experience has a positive and significant effect on trust. Trust has a positive and significant effect on intention to reuse. Trust significantly mediates the effect of experience on intention to reuse. The implications of this research can be taken into consideration for Grab management in making decisions to improve performance on the GrabFood service. Keywords: intention to reuse; experience; trust.